MANAJEMEN PENDIDIKAN ISLAM DALAM MENJAGA KUALITAS PEMBELAJARAN DI TENGAH PENDEMI COVID-19 - Wahyudi Basri, Ahmad (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2021)
This article wants to discuss how the management of Islamic education in maintaining the quality of learning in the midst of the Covid-19 pandemic. Islamic education during a pandemic must have the right management because Islamic education is not only concerned with intellectual issues but also about spiritual issues. The purpose of Islamic education is a starting ethic, so automatically the management of Islamic education must be correct. During the pandemic, the management carried out by the Ministry of Religion and its staff launched a planning, management and supervision by means of online learning. Implementers of each school along with supervision and parents and peers are the most core supervisors in Islamic education. By using qualitative methods based on previous research and several books as primary and secondary sources, it is hoped that it can make a big contribution to Islamic education and scientifically there is an image of a new file taste for future scholarship.